2014
DOI: 10.1097/mao.0b013e3182936bcf
|View full text |Cite
|
Sign up to set email alerts
|

Side-to-End Hypoglossal to Facial Anastomosis With Transposition of the Intratemporal Facial Nerve

Abstract: The HFA swingdown technique is a safe and effective method to restore facial nerve function in patients with facial paralysis and obviates the need for an interposition jump graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…Gelingt bei einem Patienten mit Neurofibromatose Typ 2 operativ eine funktionelle Erhaltung des Nervus facialis nicht, dann bietet eine direkte Transplantation im gleichen Eingriff die besten Chancen für eine Regeneration. Eine Seit-zu-End-Verbindung zwischen Hypoglossus und Fazialis innerhalb des ersten Jahres nach Fazialisparalyse kann noch immer ein ebenso gutes Ergebnis bezüglich der Rehabilitation des Gesichts erbringen [100][101][102][103][104]. Bei länger bestehenden Paresen sind plastische Rekonstruktionen mit Temporaliszügeltransfer, Tarsoraphie und Lidimplantationen ("Lid loading") zu erwägen.…”
Section: Referatunclassified
“…Gelingt bei einem Patienten mit Neurofibromatose Typ 2 operativ eine funktionelle Erhaltung des Nervus facialis nicht, dann bietet eine direkte Transplantation im gleichen Eingriff die besten Chancen für eine Regeneration. Eine Seit-zu-End-Verbindung zwischen Hypoglossus und Fazialis innerhalb des ersten Jahres nach Fazialisparalyse kann noch immer ein ebenso gutes Ergebnis bezüglich der Rehabilitation des Gesichts erbringen [100][101][102][103][104]. Bei länger bestehenden Paresen sind plastische Rekonstruktionen mit Temporaliszügeltransfer, Tarsoraphie und Lidimplantationen ("Lid loading") zu erwägen.…”
Section: Referatunclassified
“…Both nerves receive afferent input from the trigeminal reflex, and act synergistically in the coordination of some mimic and prandial functions; furthermore, both contain myelinated motor fibers with similar fascicular anatomy. 23,24 Reinnervation occurs in 4 to 12 months. Approximately 70% of the patients obtain good results, with the function of the facial nerve classified as "good", or as HB grade III.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications to the classic procedure have been proposed to improve facial function while minimizing functional deficits to the tongue. 11,12,[18][19][20][21][22][23][24][25] Several authors have reported using split hypoglossal-facial nerve techniques to reanimate the paralyzed face. 12,18 As described by Arai et al, 12 the distal hypoglossal nerve is partially divided and split longitudinally along its length to gain length for direct coaptation to the main facial nerve branch.…”
Section: Discussionmentioning
confidence: 99%
“…Several anatomic and clinic al studies have presented data on this approach 13,14,19,25,[27][28][29] Atlas and Lowinger 13 reported 3 cases of intratemporal facial nerve transposition using a similar technique, with functional recovery in all cases and a dramatic reduction in hemiglossal weakness. Recently, Slattery et al 25 described 19 patients who underwent a similar technique with 36.8% attaining House-Brackmann grade III, 47.4% a grade IV, and 15.8% a grade V result. Our experience with 20 patients using the VII to XII transposition technique shows a reliably high restoration of dynamic and static facial symmetry and excursion with minimal tongue morbidity.…”
Section: Discussionmentioning
confidence: 99%